Pengaruh Pemberian Setaria Gajah (Setariah Splendida, Stapf) dalam Ransum terhadap penampilan Ayam Broiler - Dwi Margi Suci; H.R. Anggorodi; Ignatius Kismono (Buletin Ilmu Makanan Ternak, 1987)
A feeding trial was conducted to determind the effects of incorporating Setaria Gajah (Setaria splendida, Stapf) into the diet of broiler chicks. The Setaria Gajah was added to cornsoybean meal type diets at levels of 3, 6, and 9%.Feed consumption and weight gains were reduced as the level of Setaria Gajah increased. Up to 3% Setaria Gajah was tolerated without adversely affecting performance.